IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN (SIMPEG) PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN BURU SELATAN - TUALEKA, ABDULLAH (Patria Artha Management Journal, 2021)
The purpose of conducting the research is to explain the implementation of the Personnel Management Information System at the Buru Selatan Regency Personnel and Human Resources Development Agency (BKPSDM), to analyze the driving and inhibiting factors, and to explain the steps that need to be taken in optimizing the implementation of the Human Resource Management Information System ( BKPSDM) South Buru Regency. This  study  uses  a  quantitative  and  qualitative  Monovariate  Mix  Method  approach, because it sees a fairly complex problem and the goal to be achieved is an in -depth and comprehensive understanding of the Implementation of Personnel Management Information Systems. The results showed that the Communication Indicators in the Implementation of the Personnel Management Information System (SIMPEG) between the Personnel and Human Resources Development Agency of South Buru Regency and other OPD Bodies have so far been in a position of very poor quality, bureaucratic structure in the Implementation of Management Information Systems. Staffing (SIMPEG) between the South Buru District Personnel and Human Resources Development Agency and other OPD agencies and agencies have so far been in a position of poor quality, indicators of resource utilization and utilization in the Implementation of Personnel Management Information Systems (SIMPEG) between the Personnel Agency and Development of Human Resources in South Buru Regency with other OPD Offices and Bodies has so far been in a position of poor quality and the Disposition factor in the Implementation of the Personnel Management Information System (SIMPEG) at the Personnel Agency   and Human Resource Development in Buru Selatan Regency with other OPD offices and agencies so far are in a position of poor quality.